Hearing Aids and The Quality of Life of Children with Hearing Loss - Muyassaroh, Muyassaroh; Cahyani, Nastiti Dwi; Ruspita, Dian Ayu; Dewi, Anna Mailasari Kusuma (KEMAS: Jurnal Kesehatan Masyarakat, 2022)
Hearing loss in children may cause social isolation and poor communication skills, potentially affecting mental disorders and quality of life. Hearing aids (HA) provide auditory stimuli that can improve children's speech ability and influence their quality of life. A cross-sectional study in three special schools-B (SLB-B) in Semarang was carried out. A total of 82 children (7-12 years old) with severe hearing loss with or without hearing aids were included. Quality of life was assessed by the Hearing Environments and Reflection on Quality of Life (HEAR-QL) questionnaire. The results showed that 48 (58.54%) subjects used hearing aids, and 34 (41.46%) did not use hearing aids. The average subject's age was 10.77±1.56 years old. Hearing-aid use was associated with a good quality of life of children with hearing loss (p0.001). Good quality of life was found in 68.8% of children with hearing aids compared to only 2.9% in children without hearing aids. Duration of hearing-aid use (p0.001), mother education (p0.006) was associated with good quality of life of children, whereas gender (p=0.49), number of siblings (p=0.06), and socioeconomic status (p=0.63) were not. The quality of life of children who use hearing aids is better than without hearing aids.